Adsorption and emission enhancement behavior of 4, 4′-bipyridine on dispersed montmorillonite nano-sheets under aqueous conditions. Issue 25 (20th June 2018) - Nakazato, Ryosuke; Shimada, Tetsuya; Ohtani, Yuta; Ishida, Tamao; Takagi, Shinsuke
Graphical abstract: Highlights: 4, 4′-Bipyridine (BPy) was adsorbed on an exfoliated montmorillonite nanosheet (MtNS). BPy exhibited a relatively large red shift by 30 nm in the absorption spectrum. BPy showed significant emission enhancement in the fluorescence spectrum. A wide variety of molecules could be used as a guest of MtNS host material. Abstract: The adsorption and photochemical behavior of 4, 4′-bipyridine (BPy) on an exfoliated single montmorillonite nano-sheet (MtNS) was investigated in water. Under the appropriate conditions, BPy was adsorbed on the MtNS as a monomer state. BPy exhibited a relatively large red shift by 30 nm in the absorption spectrum, and showed significant emission enhancement in the fluorescence spectrum, contrary to the non-fluorescent property of BPy in water without MtNS. From the investigation using protonated BPy (BPyH2 2+ ) under acidic conditions, it was turned out that BPy was adsorbed as BPyH2 2+ on MtNS even under neutral conditions. From the analysis based on the Langmuir adsorption isotherm, the saturated adsorption amount of BPy on MtNS was calculated to be 3.2 × 10 −2 molecule nm −2 .